Neoliberalism, the Third Way and Social Work: the UK experience - Iain Ferguson (Social Work and Society)
For most of the past two decades, the notion that there is no alternative to the market as a basis for organising society has constituted a kind of global 'common sense', accepted not only by the neo-liberal Right but also by social democratic thinkers and politicians, in the form of 'the Third Way'. This paper will critically assess the central claims of neoliberalism in the light of experience in the UK and internationally, evaluate the ways in which Third Way policies are shaping social work in the UK, and in the final section, begin to explore some of the ways in which the anti-capitalist movement which has emerged in recent years might contribute to the development of a new, engaged social work, based on social justice.